Sales Performance Management System (SPMS) for Independent Business Owner (IBO) / Nurul Izzati Mohd Yusoff - Mohd Yusoff, Nurul Izzati (Faculty of Computer and Mathematical Sciences, 2017)
Measuring performance of sales is very important in every business especially with business that has many sales representatives. This project consists on developing a Sales Performance Management system (SPMS) for Independent Business Owner (IBO). This project is a prototype for the owner of any business to manage their agent’s sales performance. The project purposed to develop a system that can solve common problem of any business owner in measuring and managing the sales person of the company. The significance of this project development is to prove that even a small team of business can have a standardize platform to measure the performance of the business. The system developed using Waterfall methodology and only four main phases among of six from the methodology framework being used. The phases consist of; Requirements Gathering, Analysis, Design and Implementation. This project work can be further extended in the concept of Human Computer Interaction (HCI) elements and with any kind of technology aided tool to enhance the user experience and make it more interactive.